Uma Análise dos Protocolos de Comunicação para Internet das Coisas - Cosmi, Arthur Brito; Mota, Vinicius F. S. (Anais do Workshop de Computação Urbana (CoUrb); 2019: Anais do III Workshop de Computação UrbanaDO - 10.5753/courb.2019.7475, 2019)
With the growth of devices connected to the Internet, several application layer protocols specific for the Internet of Things (IoT) appear every day. This high number of protocols bring doubts to developers about what to use in their projects. This work aims to assist developers in the decision making in their IoT projects. This work presents a qualitative analysis of the MQTT, MQTT-SN, CoAP and AMQP protocols. In a qualitative way, we analyzed thedomains of application and requirements of the applications to map the protocol choice. After that, the MQTT and CoAP protocols were analyzed using devices with low processing and memory capabilities. Results show that MQTT outperforms CoAP when there are several other devices accessing the same access point.